Analisis Sistem Akuntansi Pengadaan Barang Habis Pakai Pada Markas PMI Kota Madiun - Selin Manisa; Diah Hari Suryaningrum (Jurnal Akuntansi, Bisnis dan Ekonomi Indonesia (JABEI), 2025)
The purpose of this study is to analyze the accounting system for the procurement of consumables at the Madiun City Headquarters of the Indonesian Red Cross (PMI) which is an important part of the operations of a non-profit organization. Procurement of consumables, such as stationery, medicines, and other logistical needs, must be managed in an orderly manner so as not to interfere with the smooth running of humanitarian services. This research was conducted using descriptive qualitative method through interviews with related parties, as well as analysis of official procurement documents. The results showed that the procedure for submitting and approving goods at PMI Madiun City was carried out systematically. However, the recording system is still manual and not fully integrated digitally, which risks hampering the speed and accuracy of financial reporting. Therefore, it is necessary to develop a digitalized accounting system to strengthen internal control and transparency in logistics management. The findings are expected to be an input in improving the quality of consumable goods management in non-profit organizations such as PMI.